Application of graphene oxide in the adsorption and extraction of bioactive compounds from lemon peel. Issue 7 (2nd June 2021) - Sharif Nasirian, Valeh; Shahidi, Seyed‐Ahmad; Tahermansouri, Hasan; Chekin, Fereshteh
Abstract: The bioactive compounds like rutin, naringin, and gallic acid have been separated from lemon peel by graphene oxide (GO). The different influences such as pH values and separation conditions were investigated. Moreover, the samples were characterized by Fourier transform infrared spectroscopy, thermogravimetric analysis, scanning electron microscopy, UV‐Vis spectroscopy, and high‐performance liquid chromatography. The findings of high‐performance liquid chromatography revealed that the adsorbed proportion of rutin by GO was more than naringin and gallic acid so that 66.7% of rutin, 34% of naringin, and 19% of gallic acid from the extract were remarkably adsorbed and separated. Besides, adsorption percentage of these materials by GO was considered 74.8% after five cycles of adsorption–desorption process. On the other hand, we carried out batch experiments in order to study the adsorption mechanism of rutin on the GO since rutin was the highest quantity of bioactive substance in lemon peel. Pseudo‐second‐order kinetic model and Langmuir isotherm were the best models for describing adsorption process of rutin by GO. Adsorption capacity of rutin by GO was obtained about 21.08 mgg −1 . In addition, the physical adsorption of rutin by GO was confirmed by Dubinin–Radushkevich isotherm. This research confirmed that this method for separation of flavonoids is simple and less cost. Abstract : The simultaneous extraction of rutin, naringin, and gallic acid from lemon peel using GO was studied for the first time. The results showed that the adsorbed proportion of rutin by GO was more than naringin and gallic acid so that 66.7% of rutin, 34% of naringin, and 19% of gallic acid from the extract were remarkably separated.